Characterization of Vanadium-Doped BaBi4Ti4O15 Prepared by Molten KCl Salt Method - Suci Noerfaiqotul Himmah; Puspa Sari; Anton Prasetyo (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
One of the potential properties of the Aurivillius compound is photocatalyst. The four-layered Aurivillius compound BaBi4Ti4O15 has a bandgap energy of 3.2 eV caused having work function in the UV light area. The strategy to decrease the bandgap energy is doping with metal elements such as vanadium (V). In this research, vanadium-doped BaBi4Ti4O15 (BaBi4Ti4-xVxO15) (x= 0, 0.05, 0.1, and 0.15)) compounds was synthesized through the molten KCl salt method. The diffractogram samples showed that BaBi4Ti4-xVxO15 (x= 0, 0.05, 0.1, 0.15) had been successfully obtained but still found impurities  TiO2 (rutile phase) at x= 0, 0.05, 0.1, 0.15, and Bi4V2O11 at x= 0.15. The SEM image showed that the particle has plate-like morphology. The UV-Vis DRS spectrum showed that vanadium-doped BaBi4Ti4O15 has lower bandgap energy.